Investigating Postoperative Urinary Retention: Risk Factors and Postsurgical Outcomes in Total Joint Arthroplasty - Madeleine J.F. Powers, MSIII; Zachary T. Grace, MD; Barrett B. Torre, MD; Dorothy B. Wakefield, MS; Laura Sanzari, MS, BSN, RN; Matthew J. Grosso, MD (Arthroplasty Today)
Background: Postoperative urinary retention (POUR), a known complication following total joint arthroplasty (TJA), remains inconsistent in its diagnostic criteria, prevalence, and risk factors. This study aims to quantify POUR rates, identify risk factors, and assess complications associated with catheterization in TJA. Methods: A single-center cohort undergoing TJA between January 2015 and December 2022 was retrospectively reviewed. POUR rates were quantified using 3 different diagnostic criteria. Variables analyzed included age, sex, alpha-blocker prescription, operative joint, body mass index, American Society of Anesthesiologists score, Charlson Comorbidity Index classification, and anesthesia type. Complication rates between POUR and non-POUR patients were compared. Among POUR patients, 90-day postoperative renal and infectious complications were evaluated based on catheterization type and frequency. Results: Among the 17,220 TJA patients identified, POUR incidence rates varied from 20% (catheterization), 25% (postoperative bladder scan > 500 mL), to 29% (catheterization and/or bladder scan). Advanced age, male gender, lower body mass index, moderate Charlson Comorbidity Index scores, total knee arthroplasty, spinal anesthesia, and alpha-blocker use were significantly more prevalent among POUR patients. The development of postoperative complications, including renal/infectious complications, was not significant between POUR and non-POUR patients. Among POUR patients, there was a significant increase in renal/infectious complications among patients who received 4+ catheters (odds ratio = 10.17, 2.75, 37.59). Conclusions: Diagnostic variability in POUR after TJA persists. For POUR management, patients receiving 4+ catheters were at a 10-fold risk for renal/infectious complications compared to those without catheterization. Reducing catheterization frequency and employing risk stratification for susceptible patients may help mitigate these risks effectively.